First models for structural energy transmission decoupling in the high frequency regime under aerodynamic excitations. (February 2022) - Mazzeo, G; Ichchou, MN; Petrone, G; Bareille, O; De Rosa, S; Franco, F
In the wind tunnel facility, a test structure is often used for measuring its vibrational response to the aerodynamic excitation. A support is needed to sustaining the structure and it is mandatory that this support does not influence the vibrational energy to be measured. To this aim, the maximum amount of energy decoupling between the structure and the support is desired. This work is focused around a quick method to estimate this decoupling by using simplified models for the Turbulent Boundary Layer (TBL) excitation and for the structural response. Specifically, the Equivalent Rain-on-the-roof excitation is invoked with a Statistical Energy Analysis model for the structure. Some simple design rules are proposed and based on little information leading to foresee the difference of vibrational velocity levels between the two structural systems. A simplified test-case is used for the first investigations and a complex structure is finally conceived thinking to vibroacoustic measurements in a large wind tunnel facility. Although some results are largely expected, the global approach is promising.